MODEL PENGEMBANGAN KOGNITIF BERBASIS KOMPUTER DENGAN PENERAPAN PENDEKATAN REGGIO EMILIA PADA ANAK TAMAN KANAK-KANAK - Parwoto . (Universitas Negeri Makassar, 2015)
The main problem of this research is how to model computer -based cognitive development in Reggio Emilia approach developed to enhance the creative thinking of children in school . The research method used is a research and development (Research and Development ). Data collection methods used questionnaire , interview , observation and documentation. The data collected was processed by descriptive qualitative techniques to see the percentage of category level and specific dimensions of the aspects measured . Pemerian performed at the level of the needs assessment , content validation , and operational ataau empirical validation of the model. The results of the needs assessment models in general PKBK-REA - oriented game experience through the adoption of microsoft paint program , CORREL draw , and adop photo is needed in schools , especially for gifted education services . Therefore, it is urgent to develop a computer -based model of cognitive development oriented to the development of children's creative thinking abilities. The result of the analysis is limited and the class test showed that there were significant differences between the groups of children creativity of children who follow the Reggio Emelia approach and the conventional , where creativity plays a computer for the children who attend computer-based model of cognitive development Reggio Emelia approach is better than the group children who attend conventional learning . (9) PKBK - REA models and tools that have been developed effectively and efficiently in the development of kindergarten children's creativity